Children's Television Programs Report and Policy Statement. - Federal Communications Commission, Washington, DC.; Federal Communications Commission, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The Federal Communications Commission (FCC) Report and Policy Statement on Children's Television Programs summarizes the findings of a series of hearings held in response to a petition of Action for Children's Television (ACT), urging that the FCC prohibit sponsorship and commercials in children's programing, forbid product mention by program hosts and require a minimum of 14 hours' children's programs per station per week. The FCC held that elimination of commercial sponsorship was financially impractical, and refused to establish a specific number of hours for children's programs, but stated that stations have a clear obligation to provide children's programing which would be considered in license renewal. The industry was criticized for confining programing to weekends and urged to increase weekday offerings. Restrictions were placed on the number of minutes devoted to commercials and on separation of program and commercial matter. Broadcasters were given time to comply, and further review of compliance was promised. Appendixes includes an issue-oriented summary of hearing testimony, plus names of participants in public panel discussions and oral arguments. (SK)
ERIC Note: For a related document see IR 001 292.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Commercial Television; Educational Television; Federal Legislation; Programing (Broadcast); Public Policy; Television Commercials; Television Viewing; Action for Childrens Television; ACT Assessment -- Federal Communications Commission; Legal/Legislative/Regulatory Materials